Gene And Protein Expression Of Epithelial To Mesenchymal Transition For Intestinal And Anal Fistula: A Systematic Review - Nadila Haryani Osman; Ruhi Fadzlyana Binti Jailani; Hayati Binti Abd Rahman; Nazefah Abdul Hamid (Korean Society of Coloproctology, 2024)
Purpose: Intestinal fibrosis is a common complication of inflammatory bowel diseases. However, the possible involvement of epithelial-mesenchymal transition (EMT) has been scarcely investigated. This systematic review aims to search through research papers that are focusing on messenger RNA (mRNA) and protein expression profile in EMT in fistula or in intestinal fibrosis. Methods: Electronic exploration was performed until April 24, 2019 through PubMed, Ovid, Science Direct, and Scopus databases with the terms of “fistula” OR “intestinal fibrosis” AND “epithelial-mesenchymal transition”. Two independent reviewers scrutinized the suitability of the title and abstract before examining the full text that met the inclusion criteria. For each study, the sample types that were used, methods for analysis, and genes expressed were identified. The list of genes was further analyzed using DAVID (Database for Annotation, Visualization, and Integrated Discovery) and KEGG (Kyoto Encyclopedia of Genes and Genomes) pathway. Results: There were 896 citations found; however, only 3 studies fulfilled the requirements. Among the EMT-related genes, 5 were upregulated genes at mRNA level while 6 were at protein level. However, only 2 downregulated genes were found at each mRNA and protein level. Of the 4 inflammation-related genes found, 3 genes were upregulated at mRNA level and 1 at protein level. These genes were confirmed to be involved in the development of inflammatory induced fibrosis and fistula through EMT. Results from quantitative real-time polymerase chain reaction analysis were consistent with the process of EMT, confirmed by the western blot protein analysis. Conclusion: Many significant genes which are involved in the process of EMT in fistula and intestinal fibrosis have been identified. With high-end technology many more genes could be identified. These genes will be good molecular targets in the development of biomarkers for precision drug targeting in the future treatment of intestinal fibrosis and fistula.